2015
DOI: 10.1016/s1525-0016(16)33666-8
|View full text |Cite
|
Sign up to set email alerts
|

61. Vascular Smooth Muscle Cell RNA Aptamers for the Treatment of Cardiovascular Disease

Abstract: We demonstrated that this IRES is active in patients expressing the N-truncated dystrophin, raising the possibility of the therapeutic use of this isoform. To explore this we developed a novel out-of-frame exonskipping approach that uses AAV-mediated U7snRNA to efficiently skip exon 2. By injecting this AAV vector into a DMD mouse model carrying a duplication of exon 2 (Dup2), this generates a truncated reading frame, leading to activation of the IRES and synthesis of the N-truncated isoform. We now demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous studies have reported a relative low transfection efficacy to ECs. 50,51 However, high surface-mediate transfection to hard-to-transfect cells has not yet been reported. Our platform reached this highest transfection record based on the surface-mediated approach, which could potentially benefit localized gene therapy such as the gene-eluting stent.…”
Section: Acs Applied Bio Materialsmentioning
confidence: 99%
“…Previous studies have reported a relative low transfection efficacy to ECs. 50,51 However, high surface-mediate transfection to hard-to-transfect cells has not yet been reported. Our platform reached this highest transfection record based on the surface-mediated approach, which could potentially benefit localized gene therapy such as the gene-eluting stent.…”
Section: Acs Applied Bio Materialsmentioning
confidence: 99%